Efeito da adição de clorexidina na atividade antibiofilme, liberação de flúor e microdureza de cimento de ionômero de vidro - Pereira, Jesse Augusto [UNESP] (2017)
Studies have associated antimicrobial substances, such as chlorhexidine digluconate (CHX), to glass ionomer cements (GIC) with the aim of increasing its inhibitory effect on the remaining microbiota in partial caries removal procedures. However, its indication will be effective only if the incorporation of these substances does not affect the fluoride release and mechanical properties of the glass ionomer cement. Thus, the objective of this study was to evaluate the influence of CHX incorporation on the antibiofilm action, fluoride release and microhardness of glass ionomer cement. For the evaluation of the antibiofilm activity, standardized GIC specimens containing or not 1.25 and 2.5% of CHX were performed. These specimens were inserted into individual wells of polystyrene plates containing S. mutans in BHI medium with 1% sucrose. After 24h of incubation, the specimens were removed, sonicated and inserted into microtubes containing saline solution. Then, the samples were diluted and plated and after 48h of incubation, the microbial count values were obtained in CFU / ml. In order to obtain the fluoride values, GIC specimens were prepared and inserted in deionized water for 15 days and the reading was performed using a fluoride-sensitive electrode coupled in a digital pH / F analyzer. The microhardness was analyzed by means of 5 indentations in the test specimens using a Shimadzu durometer, with static load of 100g for 5s. The results showed that the antibiofilm activity of the GIC increased with the incorporation of CHX, with better results for 2.5%. The fluoride release and microhardness of GIC were not affected by the presence of CHX, regardless of their concentration. It is concluded that CHX improved the antibiofilm property of the GIC, without affecting its microhardness and ability to release fluoride